2024
DOI: 10.5534/wjmh.230091
|View full text |Cite
|
Sign up to set email alerts
|

Combined Analysis of the Transcriptome, Proteome and Metabolome in Human Cryopreserved Sperm

Longlong Fu,
Fang Fang,
Ying Guo
et al.

Abstract: Purpose This study aimed to identify the altered pathways and genes associated with freezing damage in human sperm during cryopreservation by multiomics analysis. Materials and Methods Fifteen fresh human semen samples were collected for transcriptomic analysis, and another 5 fresh human semen samples were obtained for metabolomic analysis. For each semen sample, 1 mL was cryopreserved, and another 1 mL was left untreated for paired design. The results were then combine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 20 publications
1
4
0
Order By: Relevance
“…The number of decreased transcripts in cryopreserved spermatozoa was higher than those increased compared to fresh samples. These results agree with previous studies that identified a lower abundance of transcripts in frozen and vitrified sperm than fresh samples [18,19].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The number of decreased transcripts in cryopreserved spermatozoa was higher than those increased compared to fresh samples. These results agree with previous studies that identified a lower abundance of transcripts in frozen and vitrified sperm than fresh samples [18,19].…”
Section: Discussionsupporting
confidence: 93%
“…Mitochondrial dysfunctions in sperm of different species caused by cryopreservation have been reported [6]. Also, the recent multiomics analysis performed by Fu et al [19] found that the mitochondria in cryopreserved sperm had an abnormal ultrastructure, which indicated mitochondrial dysfunction. The presence of structural and functional alterations in mitochondria from asthenozoospermic subjects confirms the important role played by these organelles in the energetic maintenance of sperm motility [30,31].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations